The Oxford handbook of private equity - Cumming, Douglas (New York ; Oxford : Oxford University Press, 2012)
This handbook provides a comprehensive picture of the issues surrounding the structure, governance and performance of private equity.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Private equity